Geographical assessment of fodder industry facilities in Basra Governorate - Ali Khalifa Al Frijat , Zeinab; Mahdi Mohammed , Faris (Basra studies journal, 2023)
Feed industry facilities in Basra Governorate witnessed great developments after it was (3) facilities during the period (1955-1965), which rose to reach (82) facilities until 2021, as a result of the increase in the number of animal breeders, especially laying and broiler chickens, and the increase in the demand for feed material for them. This led to the establishment of most of the owners of poultry farms, especially in Al-Zubayr district, to establish facilities for the manufacture of fodder within the fields to reduce economic costs and self-sufficiency.